Mydriasis caused by ESCITALOPRAM: Case report - N. Bouattour; W. Bouattour; N. Messedi; F. Charfeddine; L. Aribi; J. Aloulou (European Psychiatry, 2022)
Introduction Serotonin reuptake inhibitors (SSRIs) are the most commonly prescribed antidepressants thanks to the overall safety and tolerability spectrum. However, they can cause different side effects that not all of them are well identified.